2014
DOI: 10.5012/bkcs.2014.35.9.2749
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-based Direct Measurement of DNase I Activity with Single Stranded DNA

Abstract: Recent studies have shown that single-stranded DNA adsorbed onto graphene oxide is protected from DNase I cleavage. However, double-stranded DNA bound to graphene oxide and could be digested by DNase I. To elucidate whether single-stranded DNA is protect from DNase I in the presence of graphene oxide, this study conducted DNase I digestion using single-stranded DNA and single-stranded DNA containing the duplex region in the presence of graphene oxide. Addition of DNase I resulted in restoration of the fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This concentration is consistent with previous reports. 22 For the other two probes of P2 and P3 with stemloops, both random unpaired bases and rigid paired bases coexisted, which raised a question whether NGO can similarly quench the uorescence signal as that of P1. We then studied the interaction of NGO with P2 and P3 using the same amounts of NGO (1.2 mg) and found that the quenching efficiency of P2 and P3 were only 70% and 60%, respectively, which are much lower than that of P1 (99%) (Fig.…”
Section: Design Of a Uorescence-based Methods For Dnase Assaymentioning
confidence: 99%
“…This concentration is consistent with previous reports. 22 For the other two probes of P2 and P3 with stemloops, both random unpaired bases and rigid paired bases coexisted, which raised a question whether NGO can similarly quench the uorescence signal as that of P1. We then studied the interaction of NGO with P2 and P3 using the same amounts of NGO (1.2 mg) and found that the quenching efficiency of P2 and P3 were only 70% and 60%, respectively, which are much lower than that of P1 (99%) (Fig.…”
Section: Design Of a Uorescence-based Methods For Dnase Assaymentioning
confidence: 99%
“…In fact, the experimental condition of DNase I in sensing system was well-established to maximize the selectivity of DNase I activity for digestion of desorbed DNA specifically. Upon the application of excess amount of DNase I on DNA/GO system, it also affected on DNA strands even adsorbed on GO [42], resulting in cleavage of weakly adsorbed DNA on GO. Thus, we utilized DNase I to correlate the interaction strength between DNA and GO according to the length of DNA and the size of GO.…”
Section: Interaction Strength Between Dna and Gomentioning
confidence: 99%
“…28 The zeta potential of GO was −42.74 mV in pure water, while the potential in the reaction was −16.8 mV, indicating that more salt ions binding occurred to the surface of GO in reaction buffer. 28 For the optimal GO concentration for the adsorption of 30 nM DNA, F/F o vs. GO concentration (mg/mL) was plotted in Figure 2. F and F o represent the fluorescence intensities of DNA in the presence or absence of GO, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…According to the result of Raman spectroscopy, D peak was shown at ~1345 cm −1 and G peak at ~1600 cm −1 , denoting the presence of functional groups on the planar carbon backbones of GO (data not shown) . The zeta potential of GO was −42.74 mV in pure water, while the potential in the reaction was −16.8 mV, indicating that more salt ions binding occurred to the surface of GO in reaction buffer …”
Section: Resultsmentioning
confidence: 97%